The tetraspanin TSP3 of Neurospora crassa is a vacuolar membrane protein and shares characteristics with IDI proteins. (1st May 2016) - Heine, Daniela; Petereit, Linda; Schumann, Marcel R.; Patzelt, Diana; Rachid, Leila; Brandt, Ulrike; Werner, Antonia; Pöggeler, Stefanie; Fleißner, André
Abstract : The fungal vacuole is an organelle, which adopts pleiotropic morphologies and functions. In aging and starving hyphae it is the compartment of degradation and recycling of cellular constituents. Here we identified TSP3, one of three tetraspanins present in the filamentous ascomycete fungus Neurospora crassa, as a vacuolar membrane protein. The protein is detected only in aging and starving cultures and under other conditions, which induce autophagy, such as vegetative incompatibility or the presence of the macrolide antibiotic rapamycin. Mutant analysis revealed that TSP3 is dispensable for growth and development of the fungus under laboratory conditions. Together these findings indicate that tsp3 shares characteristics with idi (induced during incompatibility) genes and might promote vacuolar functions related to autophagy.